Gum mastic increases maspin expression in prostate cancer cells - HE, Mei-lan; CHEN, Wei-wen; ZHANG, Peng-ju; JIANG, An-li; FAN, Wei; YUAN, Hui-qing; LIU, Wen-wen; ZHANG, Jian-ye (Acta pharmacologica Sinica, 2007)
Aim： To study whether gum mastic, a natural resin, can regulate maspin expression in prostate cancer cells, and further investigate the mechanisms involved in this regulatory system. Methods： RT-PCR and Western blotting were used to detect maspin expression at the transcriptional and translational levels. Reporter gene assay was used to investigate the effect of gum mastic on the maspin promoter. The binding activity of negative androgen-responsive element （ARE） and positive Spl element in the maspin promoter were studied by electrophoretic mobility shift assay. Results： Gum mastic induced maspin mRNA and protein expression, and the maspin promoter activity was enhanced with gum mastic treatment. Finally, gum mastic inhibited the ARE binding activity and increased the Spl binding activity in the maspin promoter. Conclusion： Gum mastic enhances maspin promoter activity by suppressing ARE binding activity and enhancing Spl binding activity, and the increased activity in the maspin promoter finally leads to the upregulation of both its mRNA and protein levels.